Potret Pemertahanan Bahasa Jawa oleh Pelajar dalam Lingkup Keluarga - Azizah, Chanifatul; Satiti, Sabbihisma Debby (Sutasoma : Jurnal Sastra Jawa, 2021)
This study examines the maintenance of Javanese language by students in the family sphere in Jepangpakis, Kudus Regency and the factors that influence it. The purpose of this research is to describe the form of Javanese language maintenance by students in the family sphere in Kudus and to reveal the factors that influence it. This research uses a qualitative descriptive approach with a case study model. The data source of this study were 10 informants who were selected based on purposive sampling technique. The data of this research is in the form of informants' language data in the form of utterances which is indicated the use of Javanese language either in full or in part. The data is obtained through data collection techniques, namely interviewing, observation, listening, recording, and note-taking techniques. The collected data were analyzed using qualitative descriptive techniques and presented with formal and informal techniques. The results showed that: 1) the form of Javanese language maintenance by students in the family sphere in Kudus can be classified into: a) full Javanese utterances with two types, namely ngoko lugu and ngoko alus varieties; and b) utterances which are the result of the code mixing process of Javanese and Indonesian; 2) factors that influence the maintenance of Javanese language by informants, including: a) Javanese language shows the identity of the speaker; b) positive attitudes towards Javanese by speakers and speech partners; and c) positive attitudes towards Javanese are still found by people around the speakers. Keywords: Javanese language, students, language maintenance